ANALISIS KELAYAKAN USAHATANI BAWANG MERAH DI KELURAHAN POTA KECAMATAN SAMBI RAMPAS KABUPATEN MANGGARAI TIMUR (Feasibility Analysis of Shallot Farming in Pota Village, Sambi Rampas District, East Manggarai Regency) - Wensislaus Arman Ndau (Jurnal Ilmiah Sosio Agribis, 2024)
This research is entitled The Role of Cooperatives in Increasing Pineapple Farmer Income. This study aims to analyze the revenue, income and also the feasibility of shallot farming in Pota Village, Sambi Rampas District, East Manggarai Regency. This study used a descriptive method. The type of data is qualitative and quantitative data. Data sources are primary data and skunder data. The analysis used in this study is a business feasibility analysis including revenue, income and R/C. The results showed that the average revenue of onion farmers in one harvest season was Rp. 51,014,286. The average income of farmers in one harvest season is Rp. 32.810.394. The R/C value of 2,80, where this value is greater than 1 (2,80>1), it can be concluded that the shallot farming business in Pota Village, Sambi Rampas District, East Manggarai Regency deserves to continue.Keywords: receipts, revenue, R/C ratio, Shallots